Literasi Digital di UMKM: Tinjauan Sistematis dan Pengembangan Kerangka Teoretis Terintegrasi Menggunakan Metode PRISMA - Tamyiz, Uus Muhamad Husni; Munir; Furqon, Chairul; Dirgantari, Puspo Dewi (Jurnal Algoritma, 2025)
Digital literacy proficiency has become increasingly important for the survival and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in the digital era. This study conducts a systematic literature review following the PRISMA protocol to analyze the current state of research on digital literacy among MSMEs. Based on an analysis of fifty-six peer-reviewed articles published between 2015 and 2025 from the Scopus database, this study synthesizes existing knowledge, identifies research patterns, and proposes directions for future research. The analysis reveals a significant evolution in digital literacy research, particularly accelerated by the COVID-19 pandemic, with a notable increase from an average of one article per year during the period 2015 to 2019 to more than twelve articles per year between 2020 and 2024. Survey-based studies dominate the methodological landscape with thirty-nine point three percent, followed by quantitative approaches with nineteen point six percent. Citation analysis indicates a substantial scientific impact with a total of one thousand one hundred forty-nine citations, averaging twenty point five two citations per article. Three major research streams have emerged, namely digital transformation processes, performance impacts, and capability development. Indonesia appears as a prominent research context, representing forty-four point six percent of the studies, providing insights into the implementation of digital literacy in developing countries. The findings indicate that the successful implementation of digital literacy is influenced by technological infrastructure, organizational capability, and external support. This review contributes to theoretical development by integrating diverse perspectives and to practical applications by identifying critical success factors in digital literacy implementation. Future research opportunities include longitudinal studies, cross-country comparisons, and investigations of the effects of emerging technologies on MSME digital literacy.